MENINGKATKAN HASIL BELAJAR PEMELIHARAAN MESIN KENDARAAN RINGAN MELALUI METODE EXAMPLES NON EXAMPLES PADA SISWA KELAS XII TKR 1 SMK MUHAMMADIYAH 1 PEKANBARU TAHUN AJARAN 2018 - Nurkholis, Nurkholis (JGK (Jurnal Guru Kita), 2021)
Abstract: Improving learning outcomes of light vehicle engine maintenance through the examples non-examples method for class XII students of TKR 1 SMK Mu-hammadiyah 1 Pekanbaru in the 2018 academic year. The specific objectives of this research can be detailed as follows: To determine student learning outcomes using conventional learning models. To find out student learning outcomes using the examples non examples learning model. To find out whether there are differences in student learning outcomes using examples non-examples learning models with conventional learning models.The formulation of the problem in this study is as follows: Are there differences in student learning outcomes using examples non-examples learning models with conventional learning models? Are student learning outcomes using the examples non-examples learning model better than student learning outcomes using conventional learning models? The subject of the research is Class XII TKR 1 SMK Muhammadiyah 1 Pekanbaru Senapelan District Pekanbaru Academic year 2018 as many as 31 students. Based on the research results, it can be seen that the value of student learning outcomes in light vehicle engine maintenance learning by using examples non examples learning models is greater than the value of student learning outcomes in light vehicle engine maintenance lessons that do not use examples non examples learning models.  Keywords: Learning Machine Maintenance of Light Vehicles by using learning models Examples Non Examples Abstrak: Meningkatkan hasil belajar pemeliharaan mesin kendaraan ringan melalui metode  examples non examples pada siswa kelas XII TKR 1 SMK Muhammadiyah 1 Pekanbaru tahun ajaran 2018.Tujuan khusus dilaksanakannya penelitian ini dapat dirinci sebagai berikut: Untuk mengetahui hasil belajar siswa yang menggunakan model pembelajaran konvensional. Untuk mengetahui hasil belajar siswa yang menggunakan model pembelajaran examples non examples. Untuk mengetahui apakah terdapat perbedaan hasil belajar siswa yang menggunakan model pembelajaran examples non examples dengan model pembelajaran konvensional.Rumusan masalah dalam penelitian ini sebagai berikut: Apakah terdapat perbedaan hasil belajar siswa yang menggunakan model pembelajaran examples non examples dengan model pembelajaran konvensional? Apakah hasil belajar siswa yang menggunakan model pembelajaran examples non examples lebih baik daripada hasil belajar siswa yang menggunakan model pembelajaran konvensional?Subjek penelitian adalah Kelas XII TKR 1 SMK Muhammadiyah  1 Pekanbaru Kecamatan Senapelan Pekanbaru Tahun ajaran 2018 sebanyak 31 anak didik.Berdasarkan hasil penelitian dapat diketahui bahwa nilai hasil belajar siswa pada pembelajaran Pemeliharaan Mesin Kendaraan Ringan dengan menggunakan model pembelajaran examples non examples lebih besar daripada nilai hasil belajar siswa pada pembelajaran Pemeliharaan Mesin Kendaraan Ringan yang tidak menggunakan model pembelajaran examples non examples.